ANALISIS JUMLAH PERMINTAAN TENAGA KERJA PERHOTELAN DI DENPASAR DENGAN TREND LINIER - Ni Wayan Cahya Ayu Pratami (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Generally, it is the cultural uniqueness that is considered as one of the factors attracting both domestic and foreign tourists to come and visit Bali. The other factors increasing the number of tourists coming to Bali either for holiday or business are its beautiful landscape offering many tourist destinations and the hospitality among the Balinese. The increasing number of the tourists visiting Bali has been resulted in the increasing number of demand for hotel staffs. Denpasar is the center of the city, making it a favorite place for tourists to stay that directly affects the growth of the hotel or homestay. An estimation of the number of demand for hotel staffs in Denpasar is going to be carried out based on the data of demand for hotel staffs in 2017, by using Trend Linear Method; estimating the value of the bound variable ‘y’ when the value of the free variable ‘x’ is known. Data processing is done by using the variables with Trend Linier. The spread of and deviation of the points from the line produced are tested with the standard error of estimate. The results of the study obtained is expected to be able to help both the stakeholders deciding policy for hotel management and hotel staffs candidate. The result of data processing of demand for hotel staffs in Denpasar from 2009 to 2016 using trend linier method for 2017 until 2022, shows the number of demand with an average number of increase estimated at 200 people every year.